Outcome of Limb-sparing Surgery with Custom Mega Endoprosthesis Reconstruction for Bone Tumors in a Tertiary Care Center—10-year Study: Where Do We Stand? - Subbiah Shanmugam; Pravenkumar R Ramaswami (Journal of Orthopedics and Joint Surgery)
Background and objectives: Limb-sparing surgery with custom mega endoprosthesis reconstruction for bone tumors has been the standard of care in our institution. The purpose of this study was to ascertain the complications and their management, the ability to retain the limb despite complications, and functional outcome of the retained limb. Materials and methods: A retrospective analysis was conducted on 55 patients who, between 2013 and 2022, had undergone resection of extremity bone tumors followed by reconstruction with mega endoprosthesis. The complications were classified according to Henderson endoprosthesis failure modes. The management of these complications, rates of re-surgery, and associated limb-sparing rates were analyzed. Patients with retained limbs were rehabilitated by institutional protocol. Based on the Musculoskeletal Tumor Society (MSTS) scoring system, the functional outcome was determined. Results: The study involved 55 patients. The mean follow-up was 28 months. A total of 22 patients (40%) experienced postoperative complications, with type I (soft tissue failure) and type II (aseptic loosening) being the most common. After re-surgery, either a second limb-sparing procedure or amputation, 49 patients (89.1%) retained their limb. The mean MSTS score for these 49 patients was 77.2%. The highest scores were encountered for patients with distal femur replacement (82.1%) and lowest for proximal humerus (72.4%). Conclusion: Our study shows that despite the complications of custom mega endoprosthesis reconstruction, we have managed it with a good limb-sparing rate. The functional outcome, though reasonable, seems to have scope for improvement.